Characterization of schweinfurthinol 9-O-β-D-pyranoglucoside as a potential anti-diabetic compound via in-silico studies - Tran, Si Thanh; Phan, Thi Kim Thu; Pham, Thi Huyen Thoa; Tran, Thi Thu Huong; Dang, Xuan Du; Do, Van Chung; Truong, Ba Phong (Hue University Journal of Science: Natural Science, 2024)
Schweinfurthinol 9-O-β-D-pyranoglucoside (SP) was isolated from Euonymus laxiflorus Champ. (ELC) and found as novel α-glucosidase and α-amylase inhibitors in our previous works via experimental studies. This work aims to further characterize SP as a potential inhibitor of α-glucosidase and α-amylase and develop an anti-diabetic drug via in-silico studies. Molecular docking indicated that SP interacted with targeting enzymes α-glucosidase (Q6P7A9) and α-amylase (1SMD) with acceptable RMSD values (≤2.0 Å) and showed an efficient binding energy with DS values of –10.4 and –12.0 kcal/mol, respectively. The binding energy of SP is comparable with that of acarbose, an anti-diabetic compound, with DS values of –11.2 to –12.7 kcal/mol for enzymes Q6P7A9 and 1SMD, respectively. The analysis indicated that SP satisfied all the requirements of Lipinski’s Rules of Five while acarbose might conform to approximately 20% of Lipinski’s rules criteria. Furthermore, SP showed satisfied ADMET properties in the required permitted limit. The result of this work suggested that SP might be a potential candidate with good drug-likeness properties and a high possibility of being an anti-diabetic drug.